Innovations in Child Nutrition : The Role of Technology in Promoting Healthy Eating Habits - Hassan Rafiq Hakim; Ali Zubair; Zaid Abdul Rahman (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Childhood obesity and malnutrition are growing global concerns, and technology offers innovative solutions to promote healthy eating habits. This paper explores how technology can encourage better nutrition among children through apps, games, and digital platforms that provide personalized dietary recommendations, nutrition tracking, and educational content. The study evaluates the effectiveness of these technologies in improving children's eating habits and preventing nutrition-related health issues.